Tapering and repeated high-intensity effort ability in young elite rugby union players: influence of pretaper fatigue level - Vachon, A.; Berryman, N.; Mujika, I.; Paquet, J. B.; Bosquet, L. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To assess the effects of a short-term taper on the ability to perform repeated high-intensity efforts, depending on players` fatigue level following an intensive training block.